2015
DOI: 10.1590/2317-1545v37n2146373
|View full text |Cite
|
Sign up to set email alerts
|

Aryl removal methods and passion fruit seed positions: Germination and emergence

Abstract: -Yellow passion fruit has conquered a significant position in the agribusiness of tropical fruits; therefore, farmers have been interested in expanding their groves, and technical information that guarantees the high yield of the farmings is needed. Aiming to observe factors related to the propagative material targeted at quality and maximization of the genetic potential, the objective of the study consisted in assessing germination and emergence of passion fruit seeds collected in three positions in the fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…The fruits were taken to a laboratory and cut open. The seeds were removed, washed in running water in a nylon sieve to remove the pulp, dried for two days at room conditions to remove excess moisture, and then cleaned, and stored in a cold room at 7°C (Silva et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The fruits were taken to a laboratory and cut open. The seeds were removed, washed in running water in a nylon sieve to remove the pulp, dried for two days at room conditions to remove excess moisture, and then cleaned, and stored in a cold room at 7°C (Silva et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…A number of methods are recommended for aryl removal in passion fruit seeds such as water fermentation (Silva et al, 2015), using a blender (Ferreira et al, 2007), seed friction mixed with sand (Aguiar et al, 2014), degumming in water (Aguiar et al, 2014) and immersion in virgin lime solution (Martins et al, 2006). Implementing these techniques aims to improve the seed performance; however, some negative effects may occur due to inadequate performance of the procedures/techniques, leading to physical or physiological damage occurring.…”
Section: Introductionmentioning
confidence: 99%
“…Damage to physical and physiological quality caused to passion fruit seeds subjected to aryl removal methods is generally difficult to identify since they may not be visible and may have latent effects (Silva et al, 2015). An alternative for accurately evaluating these seeds is to use X-ray imaging analysis techniques to identify mechanical damage and seed deformations.…”
Section: Introductionmentioning
confidence: 99%
“…Plant propagation of passion fruit in commercial fields is preferentially through seeds, seminiferous (Silva et al, 2015), but lack of uniformity of germination and seedling emergence is reported by producers and nurseries, which creates difficulties in raising quality seedlings and establishing productive orchards. This lack of uniformity is related to the dormancy process present in various species of Passifloraceae, as reported by Osipi and Nakagawa (2005) in Passiflora alata Dryander, by Zucareli et al (2009) in Passiflora cincinnata Mast., and Zucareli et al (2015) in Passiflora incarnata L.…”
Section: Introductionmentioning
confidence: 99%